Effect of Silica Powder on the Bond between Building Stones and Pumice Concrete - Rjoub, Muhammad I. M. (Salehan Institute of Higher Education, 2021)
The Concrete Backed Stone (CBS) masonry structures are common in many countries in the Middle East. The weak bond and heavyweight are two main problems facing such masonry structures. In this research, Pumice Lightweight Aggregate Concrete (PLWAC) containing silica powder addition is used in backing building stones. The main objective of this research is to investigate the effect of using silica powder addition on the bond strength between building stones and the PLWAC. An experimental program is conducted to investigate the bond strength by applying a direct shear load to the concrete-stone interface. The study investigated the effect of some parameters such as the silica content, the stone surface roughness, and the concrete strength on the bond between lightweight concrete and building stones. The stone roughness comprised specimens of saw-cut and grooved stones with different groove depths. Tests showed that the bond and the compressive strength of the PLWAC increased by increasing the silica content up to 15 percent, where they start to decline. The increase in bond strength corresponding to 10 and 15 percent silica content was 14 and 33 percent, respectively. Increasing the stone roughness by about 50 percent of the saw-cut surface area provided a full bond between the building stones and their backing concrete. Furthermore, the study offered a formula that estimates the bond strength and agrees well with test results.Â Doi: 10.28991/cej-2021-03091656 Full Text: PDF